2011
DOI: 10.4269/ajtmh.2011.10-0381
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Relationship between Precipitation and Malaria Incidence in Children from a Holoendemic Area in Ghana

Abstract: Climatic factors influence the incidence of vector-borne diseases such as malaria. They modify the abundance of mosquito populations, the length of the extrinsic parasite cycle in the mosquito, the malarial dynamics, and the emergence of epidemics in areas of low endemicity. The objective of this study was to investigate temporal associations between weekly malaria incidence in 1,993 children < 15 years of age and weekly rainfall. A time series analysis was conducted by using cross-correlation function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 30 publications
(28 reference statements)
11
73
0
1
Order By: Relevance
“…Fever is also known to be accompanied by an increase of portal vein caliper (Kisauzi and Leek 1991). Since investigations have taken place after the rainy season subclinical malaria could have contributed to both the increased percentage of patients with PV dilatation and splenomegaly (Krefis et al, 2011 was neither related to overt portal fibrosis nor to splenomegaly in individual cases. Therefore it is unlikely that PV dilatation was correlated to an increase in portal pressure in the children investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Fever is also known to be accompanied by an increase of portal vein caliper (Kisauzi and Leek 1991). Since investigations have taken place after the rainy season subclinical malaria could have contributed to both the increased percentage of patients with PV dilatation and splenomegaly (Krefis et al, 2011 was neither related to overt portal fibrosis nor to splenomegaly in individual cases. Therefore it is unlikely that PV dilatation was correlated to an increase in portal pressure in the children investigated.…”
Section: Discussionmentioning
confidence: 98%
“…In the forest zone, Danuor et al [29] observed a strong negative correlation between rainfall and malaria incidence. Similarly, in the forest zone, Krefis et al [30], using a regression model, found about two-month time lag between rainfall and malaria incidence. This nonlinearity between rainfall and malaria intensity has been observed elsewhere [31,32].…”
Section: Introductionmentioning
confidence: 90%
“…6,20 Di Ghana, curah hujan mingguan berhubungan dengan insiden malaria. 21 Tinggi rendahnya curah hujan akan memengaruhi keberadaan habitat perkembangbiakan vektor malaria. Curah hujan tidak memengaruhi populasi vektor dewasa pada bulan yang sama, tetapi baru akan memengaruhi pada bulan berikutnya sesuai dengan siklus hidup nyamuk di alam.…”
Section: Pembahasanunclassified